Dicentric Y chromosome in mixed gonadal dysgenesis. - Hayek, A (1975)
A 15-year-old girl was investigated because of ambiguous genitalia. Her chromosome studies showed a 45, X/45, Xdic(Yq) mosaicism. The identity of the dicentric Y chromosome was demonstrated by its typical fluorescent banding patterns. Histological evidence of mixed gonadal dysgenesis with intragonadal tumour was observed, confirming the occurrence of gonadoblastoma associated with mosaicism in which at least one cell bears a Y chromosome.